A nano-lithium aluminum titanium phosphate solid electrolyte powder material and preparation method thereof

The solid electrolyte powder material of titanium aluminum phosphate is prepared by molecular-level mixing and spray-drying, which solves the problems of complex process, high cost and poor quality in the prior art, and achieves high quality and low cost production of the materials.

CN118610558BActive Publication Date: 2025-03-21ZHEJIANG AIKE NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410697555.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-03-21
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The prior art has problems such as complex process, high cost and poor quality when preparing solid electrolytes of titanium aluminum phosphate, including large particle size, uneven distribution, clumping after sintering, and sticking to walls.

Method used

Using a molecular-level mixed water-based precursor system, spray-drying is used to obtain a titanium aluminum lithium phosphate precursor powder, and calcining at low temperature to obtain a nano titanium aluminum lithium phosphate solid electrolyte powder material.

Benefits of technology

The material has uniform particle size distribution, uniform morphology and good spherical shape. The calcined material does not stick to the wall, does not agglomerate, and does not need to be broken. This greatly simplifies the processing technology, reduces production costs, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118610558B_ABST
    Figure CN118610558B_ABST
Patent Text Reader

Abstract

The present invention discloses a nano-titanium aluminum phosphate lithium solid electrolyte powder material and a preparation method thereof, belonging to the technical field of preparation of lithium ion battery solid electrolytes. The chemical formula of the nano-solid electrolyte material is Li1+ x Al x Ti2‑x(PO4)3, 0<x≤1, the material particles are closely arranged, the particle size is relatively uniform, and the primary particle size is 80~120nm. The present invention first prepares each raw material into a water-based precursor system in a certain manner, and then obtains the precursor of the solid electrolyte by spray drying the water-based precursor system, and finally obtains the nano-lithium titanium aluminum phosphate solid electrolyte powder material by calcining the precursor. The raw materials of the present invention are cheap and non-toxic, the synthesis process is simple, and it is easy to control. Each raw material achieves uniform mixing at the molecular level, and the produced lithium titanium aluminum phosphate solid electrolyte powder material has uniform particle size distribution, uniform morphology, good sphericity, and the calcined material does not stick to the wall, does not agglomerate, and does not need to be crushed, which greatly simplifies the processing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery solid electrolyte preparation, and in particular to a nano-lithium aluminum titanium phosphate solid electrolyte powder material and a preparation method thereof. Background Art

[0002] The development of new energy vehicles has significantly improved economic and environmental benefits, especially the development of power batteries. At present, power batteries generally use liquid electrolytes. Although they have high ionic conductivity, they still inevitably have phenomena such as heating, swelling, fire and explosion during use, which poses huge safety hazards. The development of all-solid-state batteries can effectively avoid the occurrence of such phenomena, greatly improve safety, and the energy density is also much higher than the current liquid or semi-solid batteries. Among them, the development of solid-state electrolytes is particularly noteworthy.

[0003] In solid electrolytes, NASICON-type lithium aluminum titanate phosphate Li 1+x Al x Ti 2-x (PO4)3(0<x≤1) has stable structure and high ionic conductivity (room temperature ionic conductivity>10 -4 S / cm, close to the level of commercial electrolyte), and has attracted widespread attention at home and abroad.

[0004] At present, lithium aluminum titanium phosphate 1+x Al x Ti 2-x The most important research focus of (PO4)3 is still the synthesis process and preparation method. There are many methods for preparing lithium aluminum titanium phosphate solid electrolytes, the most common of which are solid phase sintering method, coprecipitation method, sol-gel method and so on.

[0005] The solid phase method usually mixes the compounds of each element directly through dry / wet ball milling, and then sintering after treatment. Although the solid phase method has the advantages of simple process, easy control of the composition of reactants and products, and suitability for mass production, it is easy to cause uneven mixing due to the large variety of raw materials and the large differences in particle size and specific surface area between particles. The purity after sintering is not high, and it is easy to produce impure phases. In addition, long-term high-temperature sintering leads to high energy consumption, and the crystal grows too fast, resulting in a larger particle size. On the one hand, the coprecipitation method is often difficult to control the hydrolysis rate of titanium salts during the synthesis process. On the other hand, due to the large difference in the specific gravity of the raw materials, it is easy to segregate the elements during the coprecipitation process, which leads to the difficulty in controlling its morphology in the subsequent sintering process. On the other hand, it will also lead to impure crystal phases. Although the sol-gel method has mild synthesis conditions, low calcination temperature, and small synthesized particle size, the titanium source used is either expensive, toxic to the human body, or difficult to preserve, and there are safety hazards. The process is cumbersome and not conducive to large-scale production.

[0006] In addition, the above-mentioned processes generally have serious wall sticking phenomenon after sintering, and agglomerates after sintering, which need to be crushed before they can be used for subsequent treatment. The process involves high energy consumption or high material cost, which greatly increases the processing cost, and the particle size is uncontrollable, resulting in poor product quality.

[0007] In view of the problems existing in the existing preparation schemes, it is necessary to develop a preparation method for lithium titanium aluminum phosphate solid electrolyte with low cost, simple process and good quality, which is expected to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of the prior art, such as complex preparation process, high cost (expensive raw materials, sintering agglomeration, wall sticking, need for crushing, etc.), poor quality (large particle size, uneven distribution), etc., and provide a nano-lithium aluminum titanium phosphate solid electrolyte powder material and a preparation method thereof.

[0009] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a nano-lithium aluminum titanium phosphate solid electrolyte powder material, wherein the molecular formula of the solid electrolyte powder material is Li 1+x Al x Ti 2-x (PO4)3, where 0<x≤1. x can take any value between 0 and 1, such as x=0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.

[0010] In a possible implementation, it is characterized in that the primary particle size of the lithium aluminum titanium phosphate solid electrolyte powder material is 80 to 120 nm.

[0011] In a possible implementation, preferably, 0<x≤0.5;

[0012] In one possible implementation, x is 0.3, 0.4 or 0.5.

[0013] In order to solve the above technical problems, the second aspect of the present invention provides a method for preparing a nano-lithium aluminum titanium phosphate solid electrolyte powder material, comprising the following steps:

[0014] S1. Press Li 1+x Al x Ti 2-xA lithium source, an aluminum source, a phosphorus source and titanium citrate are weighed in a stoichiometric ratio of (PO4)3, and are dissolved in deionized water to obtain a lithium source aqueous solution, an aluminum source aqueous solution, a phosphorus source aqueous solution and a titanium citrate aqueous solution, respectively, wherein 0<x≤1, each substance is weighed according to its corresponding molar ratio of lithium, aluminum, titanium and phosphorus, and the lithium source is in excess of 5% to 10% to compensate for the amount lost due to volatilization of lithium at high temperature, and then the lithium source aqueous solution, aluminum source aqueous solution and phosphorus source aqueous solution are mixed and stirred until clarified to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0015] The pH of the titanium citrate aqueous solution is adjusted to 7-9 with an ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0016] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add an ammonia aqueous solution to adjust the pH to 7-9 to obtain an alkaline lithium aluminum titanium phosphate precursor aqueous solution;

[0017] S3, spray-drying the alkaline lithium aluminum titanium phosphate precursor aqueous solution obtained in step S2 to obtain lithium aluminum titanium phosphate precursor powder;

[0018] S4. The lithium titanium aluminum phosphate precursor powder obtained in step S3 is calcined to obtain a lithium titanium aluminum phosphate solid electrolyte powder material.

[0019] The conventional method for preparing nano-lithium titanium aluminum phosphate solid electrolyte powder material has the problem of uneven mixing and large particle size after sintering due to the large variety of raw materials and large specific gravity differences. Compared with the prior art, the present invention provides a nano-lithium titanium aluminum phosphate solid electrolyte powder material and a preparation method thereof. The synthesized precursor raw materials are mixed at the molecular level to ensure the uniformity of the mixing, and then the water is quickly removed by spray drying, so that the precursor molecules are composed of tiny crystal nuclei. The relatively independent tiny crystal nuclei constitute activated precursor active particles. These active particles grow slowly and relatively independently in the subsequent sintering stage, so that their morphology and particle size can be controlled.

[0020] Compared with the preparation method of the prior art, the present invention has the following beneficial effects:

[0021] The preparation method of the present invention adopts cheap inorganic salts or acids as raw materials and uses a water-based system to synthesize lithium aluminum titanium phosphate. The preparation process is simple and the cost is low. The prepared material has small particle size, narrow particle size distribution, large specific surface area, good electrochemical performance, and the particles of the produced product are closely arranged and the particle size is relatively uniform. The average primary particle size is about 100nm. The uncontrollable particle size of the product is effectively solved. The synthesized product reaches the nanometer level, and does not agglomerate or stick to the wall after sintering. Nano-scale lithium aluminum titanium phosphate powder material with uniform size can be obtained without crushing, which greatly simplifies the processing difficulty, the process is economical and environmentally friendly, the synthesized product is of high quality, the production cost is reduced, and it is suitable for industrial mass production.

[0022] In a possible embodiment, in step S1, the lithium source is selected from at least one of lithium oxide, anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium chloride, lithium nitrate, lithium formate, lithium acetate, lithium oxalate, lithium citrate, lithium phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate; the aluminum source is selected from at least one of aluminum chloride, anhydrous aluminum nitrate, aluminum nitrate nonahydrate, aluminum dihydrogen phosphate, and aluminum acetate; the phosphorus source is selected from any one or more combinations of white phosphorus, red phosphorus, black phosphorus, phosphorus trioxide, phosphorus pentoxide, phosphoric acid, metaphosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate.

[0023] In a possible embodiment, the lithium source is at least one of lithium hydroxide monohydrate, lithium nitrate, and lithium acetate; the aluminum source is at least one of aluminum chloride, aluminum nitrate nonahydrate, and aluminum dihydrogen phosphate; and the phosphorus source is at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0024] In a possible embodiment, in step S1 and step S2, the stirring temperature is 0 to 100° C., and the concentration of the ammonia solution is 5 to 28 wt %.

[0025] In a possible implementation, in step S1 and step S2, the stirring temperature is 60-75° C., and the concentration of the ammonia solution is 10-20 wt %.

[0026] In a possible implementation, in step S3, the inlet air temperature of the spray drying is 120-280°C, and the outlet air temperature is 60-120°C.

[0027] In a possible embodiment, in step S4, the calcination temperature is 650-900°C, the heating rate is 2-10°C / min, and the holding time is 0.5-6h. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings in the embodiments are described below. Obviously, the drawings are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0029] Figure 1 The process flow chart of the preparation method of nano-lithium aluminum titanium phosphate solid electrolyte powder material of the present invention;

[0030] Figure 2 The nano-lithium aluminum titanium phosphate Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 Scanning electron microscope (SEM) image of (PO4)3;

[0031] Figure 3 The nano-lithium aluminum titanium phosphate Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 X-ray diffraction (XRD) pattern of (PO4)3;

[0032] Figure 4 The nano-lithium aluminum titanium phosphate Li prepared in Example 2 1.4 Al 0.4 Ti 1.6 X-ray diffraction (XRD) pattern of (PO4)3;

[0033] Figure 5 The nano-lithium aluminum titanium phosphate Li prepared in Example 3 1.5 Al 0.5 Ti 1.5 X-ray diffraction (XRD) pattern of (PO4)3. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.

[0036] It should be noted that the numerical values ​​given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value. For example, due to the error of the weighing instrument, the weight value of each raw material for preparing the solid electrolyte material in each embodiment should be understood to have an error of ±2% or ±1%.

[0037] The present invention provides a nano-lithium aluminum titanium phosphate solid electrolyte powder material and a preparation method thereof. Figure 1 As shown: the present invention first prepares various raw materials into a water-based precursor system in a certain manner, then obtains the precursor of the solid electrolyte by spray drying the water-based precursor system, and finally obtains the nano-lithium aluminum titanium phosphate solid electrolyte powder material by calcining the precursor.

[0038] The present application is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0039] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0040] Example 1

[0041] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.3 Al 0.3 Ti 1.7 The preparation of (PO4)3 comprises the following steps:

[0042] S1. Press Li 1.3 Al 0.3 Ti 1.7 71.76 g of lithium hydroxide monohydrate (excess 10 wt%), 135 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 150 g of deionized water at 60°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0043] Press Li 1.3 Al 0.3 Ti 1.7 873.48 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 20% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0044] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 20% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor aqueous solution;

[0045] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.3 Al 0.3 Ti 1.7 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 200℃ and the outlet air temperature is 110℃;

[0046] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0047] Figure 2 The nano solid electrolyte lithium aluminum titanium phosphate Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO4)3 SEM image, from which we can see that nano-titanium aluminum phosphate Li 1.3 Al 0.3 Ti 1.7 The particles of (PO4)3 powder material are closely arranged and the particle size is relatively uniform, with the average primary particle size being about 100nm.

[0048] Figure 3 The nano solid electrolyte lithium aluminum titanium phosphate Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 XRD spectrum of (PO4)3. It can be seen from the figure that the diffraction peak position of the sample is consistent with the standard card of LiTi2(PO4)3, and there are no diffraction peaks of other substances, indicating that the sample is of high purity and free of impurities.

[0049] Example 2

[0050] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.4 Al 0.4 Ti 1.6 The preparation of (PO4)3 comprises the following steps:

[0051] S1. Press Li 1.4 Al 0.4 Ti 1.6 77.28 g of lithium hydroxide monohydrate (excess 10 wt%), 180 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 175 g of deionized water at 60°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0052] Press Li 1.4 Al 0.4 Ti 1.6 822.1 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 20% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0053] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 20% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor aqueous solution;

[0054] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.4 Al 0.4 Ti 1.6 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 200℃ and the outlet air temperature is 110℃;

[0055] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0056] Figure 4 The nano solid electrolyte lithium aluminum titanium phosphate Li prepared in Example 2 1.4 Al 0.4 Ti 1.6 XRD spectrum of (PO4)3. It can be seen from the figure that the diffraction peak position of the sample is consistent with the standard card of LiTi2(PO4)3, and there are no diffraction peaks of other substances, indicating that the sample is of high purity and free of impurities.

[0057] Embodiment 3:

[0058] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.5 Al 0.5 Ti 1.5 The preparation of (PO4)3 comprises the following steps:

[0059] S1. Press Li 1.5 Al 0.5 Ti 1.5 82.8 g of lithium hydroxide monohydrate (excess 10 wt%), 225 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 200 g of deionized water at 60°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0060] Press Li 1.5 Al 0.5 Ti 1.5 770.72 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 20% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0061] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 20% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor aqueous solution;

[0062] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.5 Al 0.5 Ti 1.5 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5(PO4)3 precursor powder. The inlet air temperature of the spray drying is 200℃ and the outlet air temperature is 110℃;

[0063] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0064] Figure 5 The nano solid electrolyte lithium aluminum titanium phosphate Li prepared in Example 3 1.5 Al 0.5 Ti 1.5 XRD spectrum of (PO4)3. It can be seen from the figure that the diffraction peak position of the sample is consistent with the standard card of LiTi2(PO4)3, and there are no diffraction peaks of other substances, indicating that the sample is of high purity and free of impurities.

[0065] Example 4

[0066] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.3 Al 0.3 Ti 1.7 The preparation of (PO4)3 comprises the following steps:

[0067] S1. Press Li 1.3 Al 0.3 Ti 1.7 59.16 g of lithium nitrate (excess 10 wt%), 135 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 150 g of deionized water at 75°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0068] Press Li 1.3 Al 0.3 Ti 1.7 873.48 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 15% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0069] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 15% ammonia aqueous solution to adjust the pH to 8.5 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor aqueous solution;

[0070] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.3 Al 0.3 Ti 1.7 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 180℃ and the outlet air temperature is 100℃;

[0071] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0072] Example 5

[0073] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.4 Al 0.4 Ti 1.6 The preparation of (PO4)3 comprises the following steps:

[0074] S1. Press Li 1.4 Al 0.4 Ti 1.6 63.71 g of lithium nitrate (excess 10 wt%), 180 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 200 g of deionized water at 75°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0075] Press Li 1.4 Al 0.4 Ti 1.6822.1 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 10% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0076] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 10% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor aqueous solution;

[0077] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.4 Al 0.4 Ti 1.6 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 185℃ and the outlet air temperature is 95℃;

[0078] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0079] Embodiment 6:

[0080] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.5 Al 0.5 Ti 1.5 The preparation of (PO4)3 comprises the following steps:

[0081] S1. Press Li 1.5 Al 0.5 Ti 1.5 68.26 g of lithium nitrate (excess 10 wt%), 225 g of aluminum nitrate nonahydrate and 414.66 g of 85% phosphoric acid solution were weighed and dissolved in 250 g of deionized water at 65°C, and stirred at this temperature until clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0082] Press Li1.5 Al 0.5 Ti 1.5 770.72 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 10% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0083] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 10% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor aqueous solution;

[0084] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.5 Al 0.5 Ti 1.5 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 180℃ and the outlet air temperature is 100℃;

[0085] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0086] Example 7

[0087] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.3 Al 0.3 Ti 1.7 The preparation of (PO4)3 comprises the following steps:

[0088] S1. Press Li 1.3 Al 0.3 Ti 1.756.62 g of lithium acetate (excess 10 wt%), 135 g of aluminum nitrate nonahydrate and 414.09 g of ammonium dihydrogen phosphate were weighed and dissolved in 2000 g of deionized water at 60°C and stirred at this temperature until the solution became clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0089] Press Li 1.3 Al 0.3 Ti 1.7 873.48 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 15% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0090] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 15% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor aqueous solution;

[0091] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.3 Al 0.3 Ti 1.7 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 200℃ and the outlet air temperature is 110℃;

[0092] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.3 Al 0.3 Ti 1.7 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3 solid electrolyte powder material. The calcination temperature is 800℃, the heating rate is 5℃ / min, and the holding time is 2h.

[0093] Example 8

[0094] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.4 Al 0.4 Ti 1.6 The preparation of (PO4)3 comprises the following steps:

[0095] S1. Press Li1.4 Al 0.4 Ti 1.6 60.98 g of lithium acetate (excess 10 wt%), 180 g of aluminum nitrate nonahydrate and 414.09 g of ammonium dihydrogen phosphate were weighed and dissolved in 2500 g of deionized water at 60°C and stirred at this temperature until the solution became clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0096] Press Li 1.4 Al 0.4 Ti 1.6 822.1 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 20% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0097] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 20% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor aqueous solution;

[0098] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.4 Al 0.4 Ti 1.6 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 180℃ and the outlet air temperature is 100℃;

[0099] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.4 Al 0.4 Ti 1.6 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder material. The calcination temperature is 800℃, the heating rate is 5℃ / min, and the holding time is 1h.

[0100] Example 9

[0101] Nano-solid electrolyte Lithium titanium aluminum phosphate 1.5 Al 0.5 Ti 1.5The preparation of (PO4)3 comprises the following steps:

[0102] S1. Press Li 1.5 Al 0.5 Ti 1.5 65.33 g of lithium acetate (excess 10 wt%), 225 g of aluminum nitrate nonahydrate and 414.09 g of ammonium dihydrogen phosphate were weighed and dissolved in 3000 g of deionized water at 75 ° C. and stirred at this temperature until the solution was clear to obtain a lithium-aluminum-phosphorus composite aqueous solution;

[0103] Press Li 1.5 Al 0.5 Ti 1.5 770.72 g of titanium citrate was weighed and dissolved in deionized water at 75°C with stirring, and then the pH was adjusted to 7.5 with 20% ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution;

[0104] S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution obtained in step S1 at 75°C, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add 20% ammonia aqueous solution to adjust the pH to 8 to obtain a clear and transparent alkaline lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor aqueous solution;

[0105] S3, the alkaline aluminum titanium phosphate Li obtained in step S2 1.5 Al 0.5 Ti 1.5 The (PO4)3 precursor aqueous solution was spray dried to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor powder. The inlet air temperature of the spray drying is 220℃ and the outlet air temperature is 110℃;

[0106] S4, the lithium aluminum titanium phosphate Li obtained in step S3 1.5 Al 0.5 Ti 1.5 (PO4)3 precursor powder is calcined to obtain lithium aluminum titanium phosphate Li 1.5 Al 0.5 Ti 1.5 (PO4)3 solid electrolyte powder material. The calcination temperature is 750℃, the heating rate is 5℃ / min, and the holding time is 4h.

[0107] Although exemplary embodiments are described above, it is not intended that these embodiments describe all possible forms covered by the claims. The words used in the specification are descriptive rather than restrictive, and it should be understood that various changes can be made without departing from the spirit and scope of the present disclosure. As previously mentioned, the features of various embodiments can be combined to form other embodiments of the present invention that may not be explicitly described or shown. Although various embodiments may have been described as providing advantages or being preferred in terms of one or more required characteristics relative to other embodiments or prior art embodiments, it will be appreciated by those of ordinary skill in the art that one or more features or characteristics can be compromised to achieve a desirable overall system attribute, which depends on the specific application and the specific implementation. These attributes may include, but are not limited to, cost, strength, durability, life cycle cost, marketability, appearance, packaging, size, maintainability, weight, manufacturability, ease of assembly, etc. Therefore, embodiments described as less desirable than other embodiments or prior art embodiments in terms of one or more characteristics are not outside the scope of the present disclosure, and may be desirable for a particular application.

[0108] The invention provides a method for preparing a nano-lithium titanium aluminum phosphate solid electrolyte powder material with a simple synthesis process and easy control. The invention first prepares each raw material into a water-based precursor system in a certain manner, then spray-dries the water-based precursor system to obtain the precursor of the solid electrolyte, and finally calcines the precursor to obtain the nano-lithium titanium aluminum phosphate solid electrolyte powder material. The invention has a simple synthesis process and is easy to control. Each raw material is uniformly mixed at the molecular level. The produced lithium titanium aluminum phosphate solid electrolyte powder material has a uniform particle size distribution, uniform morphology, good sphericity, and the calcined material does not stick to the wall, does not agglomerate, and does not need to be crushed, which greatly simplifies the processing technology. In the reaction process of the preparation method of the invention, each raw material is uniformly mixed at the molecular level. The produced lithium titanium aluminum phosphate solid electrolyte powder material has a uniform particle size distribution, uniform morphology, good sphericity, and the calcined material does not stick to the wall, does not agglomerate, and does not need to be crushed, which greatly simplifies the processing technology. In the preparation process of the lithium titanium aluminum phosphate solid electrolyte powder material described in the present invention, cheap inorganic salts are used as raw materials, and a water-based system is adopted, which can reduce the equipment requirements and environmental protection requirements in the industrial scale-up production process, shorten the time consumption, increase the yield, effectively reduce the production cost, and do not have a negative impact on the material. It is easy to industrialize, and the prepared lithium titanium aluminum phosphate solid electrolyte material is of high quality.

[0109] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered by the scope of the claims and specification of the present invention.

Claims

1. A method for preparing nano-lithium aluminum titanium phosphate solid electrolyte powder material, characterized in that: The molecular formula of the solid electrolyte powder material is Li 1+x Al x Ti 2-x (PO4)3, where 0<x≤1; The preparation method comprises the following steps: S1. Press Li 1+x Al x Ti 2-x A lithium source, an aluminum source, a phosphorus source and titanium citrate are weighed in a stoichiometric ratio of (PO4)3, and are dissolved in deionized water to obtain a lithium source aqueous solution, an aluminum source aqueous solution, a phosphorus source aqueous solution and a titanium citrate aqueous solution, respectively. Each substance is weighed according to the corresponding molar ratio of lithium, aluminum, titanium and phosphorus, and the lithium source is in excess of 5% to 10% to compensate for the amount lost due to volatilization of lithium at high temperature. Subsequently, the lithium source aqueous solution, the aluminum source aqueous solution and the phosphorus source aqueous solution are mixed and stirred until clarified to obtain a lithium-aluminum-phosphorus composite aqueous solution; The pH of the titanium citrate aqueous solution is adjusted to 7-9 with an ammonia solution to obtain a clear and transparent alkaline titanium citrate aqueous solution; S2, adding the lithium-aluminum-phosphorus composite aqueous solution obtained in step S1 to the alkaline titanium citrate aqueous solution, stirring and dissolving to obtain an acidic lithium aluminum titanium phosphate precursor aqueous solution, and then continuing to add an ammonia aqueous solution to adjust the pH to 7-9 to obtain an alkaline lithium aluminum titanium phosphate precursor aqueous solution; the precursor raw materials are mixed at the molecular level to ensure the uniformity of the raw material mixing; S3, spray-drying the alkaline lithium titanium aluminum phosphate precursor aqueous solution obtained in step S2 to obtain lithium titanium aluminum phosphate precursor powder; the precursor powder obtained by spray drying is still mixed at the molecular level, which can ensure the uniformity of subsequent sintering and is conducive to controlling the morphology and particle size; S4, calcining the lithium aluminum titanium phosphate precursor powder obtained in step S3 to obtain a lithium aluminum titanium phosphate solid electrolyte powder material; In the step S1 and the step S2, the stirring temperature is 60-75°C, and the concentration of the ammonia solution is 10-20wt%; In the step S3, the inlet air temperature of the spray drying is 120-280°C, and the outlet air temperature is 60-120°C; in the step S4, the calcination temperature is 650-900°C, the heating rate is 2-10°C / min, and the insulation time is 0.5-6 h.

2. The method for preparing nano-lithium aluminum titanium phosphate solid electrolyte powder material according to claim 1, characterized in that: 0<x≤0.5, and the primary particle size of the solid electrolyte powder material is 80-120 nm.

3. The method for preparing nano-lithium aluminum titanium phosphate solid electrolyte powder material according to claim 1, characterized in that: x is 0.3, 0.4 or 0.

5.

4. The method for preparing nano-lithium aluminum titanium phosphate solid electrolyte powder material according to claim 1, characterized in that: In the step S1, the lithium source is selected from at least one of lithium chloride, lithium nitrate, lithium formate, lithium acetate, lithium oxalate, lithium citrate, lithium phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate; the aluminum source is selected from at least one of aluminum chloride, anhydrous aluminum nitrate, aluminum nitrate nonahydrate, aluminum dihydrogen phosphate, and aluminum acetate; the phosphorus source is selected from any one or more combinations of phosphoric acid, metaphosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate.

5. The method for preparing nano-lithium aluminum titanium phosphate solid electrolyte powder material according to claim 4, characterized in that: The lithium source is at least one of lithium nitrate and lithium acetate; the aluminum source is at least one of aluminum chloride, aluminum nitrate nonahydrate, and aluminum dihydrogen phosphate; and the phosphorus source is at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

Citation Information

Patent Citations

  • Quasi-solid electrolyte as well as preparation method and application thereof

    CN108365260A

  • Method for preparing lithium aluminum titanium phosphate solid electrolyte step by step and application

    CN117049497A